(untitled) (Journal of Nepal Physical Society, 2022)
The Free energy of mixing, Heat of mixing and Viscosity of Na-K alloy are investigated theoretically at different temperatures using the Regular solution model. The interaction energy is temperature dependent. The theoretical values of interchange energy at different temperatures are obtained by best fit parameter approximation with the help of experimental values at 384K. The properties have been studied with the help of computed theoretical interchange energy at different temperatures using interchange energy and temperature relation. A comparison of theoretical and experimental values at 384K shows that they are in good agreement and using this basis we have computed the values at different temperatures.